" POLITENESS STRATEGIES IN UZBEK " ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
Politeness is a fundamental pragmatic phenomenon that regulates interpersonal communication and reflects the sociocultural values of a speech community. This article investigates politeness strategies in the Uzbek language from a pragmatic and sociolinguistic perspective, aiming to reveal how cultural norms, social hierarchy, and collective values shape communicative behavior. Drawing on classical politeness theories, particularly Brown and Levinson’s face theory, the study analyzes Uzbek politeness strategies as a system of linguistic and extralinguistic mechanisms designed to maintain social harmony and mutual respect.